Clean Water Initiative for Health and Nutrition. A Case Study of Bungoma County - Lutta , Samson M.; Kituyi , Lusweti (African Journal of Education,Science and Technology (AJEST), 2023)
Water, especially in rural areas is normally found contaminated cause of inadequate protection of water points both surface and underground due to poor hygiene practices. Water contaminants contributes to various chronic communicable diseases that affects humanity. Convention methods applied for water treatment remain expensive, unreliable and inaccessible for majority in developing countries. A study was done to determine the potential of hydrogen (pH) and microbial assay of water samples from different sources in Bungoma county. The water samples were collected from various part and obtained from different sources. The parameter used to test water quality were pH instrumentally and total bacterial count for microbial assay done using pour plate isolation technique. The efficiency of ultra violet radiation from natural sunlight as bactericide was determined using WADI equipment. The total bacterial counts in the samples were compared after sterilization with the results showing notable difference between treated and untreated samples. Majority of the treated water samples with exception of one were within allowable limit for non-pathogenic colonies for drinking water of 100 colonies per ml. pH of most the water samples was found to be acidic and values not within the recommended WHO acceptable limits of between 6.5 to 8.6. The values of parameters used to assess water quality from the various samples were analysed using R analytics and found to be significantly different (p < 0.05).The results obtained showed that the quality of most water sources did not conform to the required standard for domestic water hence need for remediation process and public sensitization of the community.